Health-related quality of life in adults with HIV/AIDS: Comparison of MOSSF-36, WHOQOL-BREF and WHOQOL-HIV-BREF, Medellin, Colombia, 2009 (Colombia Medica, 2011)
Introduction: In Colombia, there are few studies that have evaluated the health-related quality of life (HRQOL) of individuals infected with HIV/AIDS through MOSSF-36, WHOQOL-BREF or WHOQOL-HIV-BREF and no studies have been reported comparing some of its psychometric properties.Objective: To describe the HRQOL and to analyze the psychometric properties of two generic and one specific instruments to measure HRQOL in a group of people living with HIV/AIDS in Medellin, Colombia, 2009.Methodology: Cross-sectional study in a nonrandom sample of 187 subjects with HIV/AIDS. The MOSSF-36, WHOQOL-BREF, and WHOQOL-HIV-BREF were applied. The description was made with proportions and summary measures; reliability was assessed with Cronbach's alpha, Pearson's correlation coefficients were used for internal consistency and discriminant validity, and the convergent/divergent validity of the concepts of HRQOL with the correlation among the domains of the instruments.Results: Higher HRQOL scores were observed in Physical Function, Environment, Level of Independence and Spirituality. The MOSS-36 showed an excellent level of reliability, internal consistency and discriminant validity in its eight domains; the WHOQOL-BREF presented excellent psychometric properties in Physical Health, Environment and Social Relations, and good properties in Psychological Health; whereas, the WHOQOL-HIV-BREF had excellent psychometric properties in Social Relations, Environment, Spirituality and Independence and good properties in Physical and Psychological Health. There were correlations above 0.4 among domains of different instruments, which show the convergence of the measurement of HRQOL with the instruments applied.Conclusion: The MOSSF-36 showed a perfect profile of psychometric characteristics, the WHOQOL-BREF and WHOQOL-HIV-BREF were an acceptable level and the constructs of the three instruments converge, indicating good development of tools for studying HRQOL in HIV/AIDS infected individuals in Colombia.